Father absence and its effect on young adults’ choices of cohabitation, marriage and divorce - Thorne, David R. (Kansas State University, 2009)
Fathers, once deemed as “forgotten contributors to child development” (Lamb, 1975, p. 246), may provide more than just a bread winning role for their children. More studies have examined the effects of a father’s absence and involvement on his children, specifically among adolescents’ early sexual activity. The purpose of this study was to examine the influence of father absence on young adults’ choices of cohabitation, marriage and divorce. The data for this analysis came from The February-March 2007 Social Trends Survey by the Pew Research Center, a nationally representative sample in the United States. This analysis selected 802 young adult respondents (ages 18-40 year old). Results support previous research that the two key factors leading to father absence are children whose parent never married or whose parents divorced. Father absence was associated with children's future cohabitation rates for the whole sample, but not when examined individually by gender, race or ethnicity. Higher marriage rates were associated with father-present homes among men and in the overall sample, but not for women or according to race or ethnicity. No associations were found between father absence and children's future divorce rates. Tracking young adults’ rates of marriage and divorce according to father absence and cohabitation (tables 4.4 through 4.9) found that young adults who had the combination of a father-present and did not cohabit had the lowest divorce rates. Future research should investigate the disparity in father-present homes between those who did and did not cohabit, father and child religiosity, and father involvement. Implications for family life education were also presented.
Keywords: father absence; cohabitation; marriage; divorce; father; family; Education, Social Sciences (0534); Psychology, General (0621); Sociology, Individual and Family Studies (0628)